Design and Kinematics Analysis of Novel Uncoupled Two-translational Parallel Mechanism - Fenglin Lu; Yanbin Zhang; Keming Wang; Xuemin Wei (Jixie chuandong)
Aiming to solve the strong coupling problem of parallel mechanism， a novel uncoupled two-translational parallel mechanism is proposed， which includes three branch chains. The first and the second branch chains have the same structure， they are all RURR-type structures. The third branch chain， called a pure constraint branch， is composed of three rotational joints whose axes are with parallel to each other. Based on the screw theory， the degree of freedom and output motion characteristics of the mechanism are analyzed. The kinematics models of the mechanism are established by using the actuation screw wrench theory and the closed loop vector method. Position， velocity and acceleration equations are derived. Singularity is also analyzed in detail and the singular configurations of the mechanism are obtained. The kinematics simulation is performed by using Matlab and Adams software. The correctness of the theoretical analysis is verified by the simulation results.